Nucleotide metabolism-related host proteins RNA polymerase II subunit and uridine phosphorylase 1 interacting with porcine epidemic diarrhea virus N proteins affect viral replication - Xu, Yifan; Yi, Heyou; Kuang, Qiyuan; Zheng, Xiaoyu; Xu, Dan; Gong, Lang; Yang, Liangyu; Xiang, Bin (Frontiers in Veterinary Science, 2024)
Porcine epidemic diarrhea virus (PEDV) is a highly infectious pathogen that targets pig intestines to cause disease. It is globally widespread and causes huge economic losses to the pig industry. PEDV N protein is the protein that constitutes the core of PEDV virus particles, and most of it is expressed in the cytoplasm, and a small part can also be expressed in the nucleus. However, the role of related proteins in host nucleotide metabolic pathways in regulating PEDV replication have not been fully elucidated. In this study, PEDV-N-labeled antibodies were co-immunoprecipitated and combined with LC-MS to screen for host proteins that interact with N proteins. Bioinformatics analyses showed that the selected host proteins were mainly enriched in metabolic pathways. Moreover, co-immunoprecipitation and confocal microscopy confirmed that the second-largest subunit of RNA polymerase II (RPB2) and uridine phosphorylase 1 (UPP1) interacted with the N protein. RPB2 is the main subunit of RNA polymerase II and plays an important role in eukaryotic transcription. UPP1 is an enzyme that catalyzes reversible phosphorylation of uridine to uracil and ribo-1-phosphate to promote catabolism and bio anabolism. RPB2 overexpression significantly promoted viral replication, whereas UPP1 overexpression significantly inhibited viral replication. Studies on interactions between the PEDV N and host proteins are helpful in elucidating the pathogenesis and immune escape mechanism of PEDV.